Biotechnology of yeasts and filamentous fungi - Sibirny, Andriy A. (Springer, 2020)
This book provides a comprehensive overview on biotechnological applications of unicellular and multicellular fungi in a variety of industrial branches. Targeted genetic and metabolic engineering of fungi allows production of native and transgenic enzymes and proteins in industrial scales. Those most prominently find application in biorefineries for the production of value-added chemicals and biofuels, in the pharmaceutical industry as well as in biomedicine. Each chapter is dedicated to applications and potential beneficial use of particular strains of yeasts and filamentous fungi and their produced biomolecules. The book targets researchers from both academia and industry and graduate students working in microbial biotechnology.